Characteristic of Rats as Reservoirs of Leptospirosis - Marbawati, Dewi; Harilsmanto, Harilsmanto; Pramestuti, Nova (Universitas Ahmad Dahlan, 2016)
Background: Globally, the incidence of leptospirosis was â¥500.000 cases especially in Indonesia, the mortality rate of lesptospirosis reached >5% in 2004-2012. Two suspected cases are found in Banyumas area since 2010 to May 2014 The purpose of this study was to identify the reservoir of leptospirosis. Method: The study was cross-sectional. The Location conducted in Kedung Pring village, Kemranjen sub district and Beji village, Kedung Banteng sub district in Banyumas. Results: The species of rats are called Rattus tanezumi and Suncus murinus, however Mus musculus is found in Beji village. The trap of rat was succed in each location was 15% for Beji Village kedung Banteng sub district and 14.14% for Kedung Pring village, Kemranjen sub district. Conclusion: All of species rats that are potentially transmitted for leptospirosis.